De novo hepatocellular carcinoma in a non‐cirrhotic allograft 27 years after liver transplantation: A case report. Issue 5 (23rd January 2021) - El‐domiaty, Nada; Saliba, Faouzi; Sebagh, Mylène; Salloum, Chady; Vibert, Eric; Azoulay, Daniel; Hamelin, Jocelyne; Cherqui, Daniel; Adam, René; Samuel, Didier
Abstract : Hepatocellular carcinoma recurrence after liver transplantation is a well‐known complication but the development of de novo hepatocellular carcinoma in non‐cirrhotic allograft with no previous history of hepatic malignancy either in the donor or the recipient is extremely rare. A 33‐year‐old man underwent deceased donor liver transplantation due to HBV‐HDV cirrhosis in 1991. The donor was healthy, with negative viral serology. Pretransplant assessment and explant liver pathology revealed no tumor. He developed an 8 cm mediastinal thymus cancer in 2014, a chronic myeloid leukemia in 2015 and a 16 mm renal cell carcinoma in 2017. After 27 years, in 2018, his routine follow‐up sonography showed incidentally a 37 mm hepatic nodule in segment VII which revealed after percutaneous liver guided biopsy a hepatocellular carcinoma. As no extra hepatic metastasis was noted, segmentectomy was done. The pathological report confirmed a moderately differentiated hepatocellular carcinoma nodule of 50 mm diameter with absence of microvascular invasion and the non‐tumoral liver showed histological features of NASH (SAF score: S1A2F3, NAS score: A3F3 and LAFSc:5) with absence of HBsAg and HBcAg. This case emphasizes the importance of long‐term close surveillance by imaging of the graft even in the absence of viral recurrence and graft cirrhosis. Abstract : The authors summarize cases of de novo hepatocellular carcinoma in liver allografts, emphasizing the harmful effect of long‐term immunosuppression exposure and the importance of long‐term surveillance for malignancy, even in the absence of allograft cirrhosis.